Erratum to: Half-a-century (1971-2020) of glacier shrinkage and climatic variability in the Bhaga basin, western Himalaya - Das, Suresh; Sharma, Milap Chand; Murari, Madhav Krishna; Nüsser, Marcus; Schmidt, Susanne (Journal of mountain science, 2023)
The original online version of this article was revised. The position of the watershed names “Bhaga Upper” and “Bhaga Lower” were erroneously placed in Fig. 10 in the original article. Fig. 10 has been corrected as follows.
Gesehen am 25.05.2023